Treatment options for massive rotator cuff tears: a narrative review - Di Benedetto, Paolo; Mancuso, Francesco; Tosolini, Luca; Buttironi, Michele Mario; Beltrame, Alessandro; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2021)
The treatment of massive rotator cuff tears poses a challenge to orthopedic surgeons. The prevalence of massive rotator cuff tears is 40% of all rotator cuff tears. Compared with smaller tears, massive rotator cuff tears are often complicated by structural failure and poor outcomes and present a higher rate of recurrent tearing after surgical repair. Several management options are available but the selection of the most appropriate treatment for each patient can be challenging. To achieve the best outcomes, the orthopedic surgeon should have a good understanding of the indications, the pathomechanics and the clinical outcomes of the various treatment modalities. Treatment options include non-operative management, arthroscopic debridement with a biceps tenotomy or tenodesis, complete or partial repair, patch augmentation, superior capsular reconstruction, muscle/tendon transfer and reverse total shoulder arthroplasty. The purpose of this article is to review treatment options and clinical outcomes for the management of massive rotator cuff tears.